Implications of Brazilian Institutional Guidelines on educational efficiency - Marcus Gerardus Lavagnole; Kalinca Lea Becker; Mário Jorge Cardoso de Mendonça (Institute for Applied Economic Research (ipea), 2020)
This paper aims to investigate the relation between inefficiency in the Brazilian education system and municipal wealth, discussing how the actual legislation possibly influences it. To that end, we apply a stochastic frontier model which accommodates covariates in the asymmetric error component to analyze the impact of the GDP per capita on the inefficiencies. This methodology is applied to a panel dataset from the Metropolitan area of Porto Alegre municipalities over the period 2007-2017. The results indicate a positive effect, suggesting that richer municipalities are less efficient in allocating their resources.
Keywords: I20; H75; D61; C11; 330; educational inefficiency; Fundeb; stochastic frontier analysis; Bayesian inference